Multilevel Analysis: Contextual Effects of School and Psychosocial Determinants on Healthy Sexual Behavior of High School Adolescents in Banyuwangi, East Java, Indonesia - Lia Ulfah Luthfiana; Pawito Pawito; Eti Poncorini Pamungkasari (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Along with the development of the era, teenagers began to be faced with various problems and the biggest problems faced by teenagers were sexual problems. Sexual behavior in adolescents who are carried out actively poses a risk of teenage pregnancy and transmission of sexually transmitted diseases. This study aims to analyze the influence related to school context and psychosocial determinants on healthy sexual behavior of adolescents at the age of 15-19 years in Banyuwangi Regency.Subjects and Method: This study used a cross sectional research design. The study was conducted in 25 high schools/vocational high schools in Banyuwangi Regency, East Java in August to September 2020. Sampling of 225 adolescents was carried out using stratified random sampling and simple random sampling. The dependent variable is healthy sexual behavior. The independent variables include knowledge, self-efficacy, parental support, sources of information/technology, perception of seriousness. Data were collected using a questionnaire. Data were analyzed using multiple logistic regression with Stata 13.Results: Adolescents will have healthy sexual behavior with high knowledge about healthy sexual behavior (b= 0.23; 95% CI= 0.05 to 0.41; p= 0.014), have strong self-efficacy (b= 0.14; 95% CI= 0.01 to 0.27; p= 0.035), had good parental support (b= 0.21; 95% CI= 0.09 to 0.34; p = 0.001), had high exposure to information sources (b= 0.36; 95% CI= 0.15 to 0.56; p = 0.001 ), and had a high perception of seriousness for weak sexual behavior (b= 0.82; 95% CI= 0.45 to 1.19; p <0.001). There is an effect of school level on healthy sexual behavior with an ICC of 16.4%.Conclusion: Healthy sexual behavior in adolescents can increase with high knowledge, strong self-efficacy, having exposure to high sources of information, and having a high perception of seriousness. There is an effect of school level on healthy sexual behavior.Keywords: healthy sexual behavior, school contextual, psychosocial determinants, adolescentsCorrespondence: Lia Ulfah Luthfiana. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36 A, Surakarta, 57126. Email: luthfianalia7@gmail.com. Mobile: +6285236800700.Journal of Health Promotion and Behavior (2021), 06(03): 188-200DOI: https://doi.org/10.26911/thejhpb.2021.06.03.03